Global Emergency Medicine: A Review of the Literature From 2017. (14th June 2018) - Becker, Torben K.; Trehan, Indi; Hayward, Alison Schroth; Hexom, Braden J.; Kivlehan, Sean M.; Lunney, Kevin M.; Modi, Payal; Osei‐Ampofo, Maxwell; Pousson, Amelia; Cho, Daniel K.; Levine, Adam C.; ,
Abstract: Objectives: The Global Emergency Medicine Literature Review (GEMLR) conducts an annual search of peer‐reviewed and gray literature relevant to global emergency medicine (EM) to identify, review, and disseminate the most important new research in this field to a global audience of academics and clinical practitioners. Methods: This year, 17, 722 articles written in three languages were identified by our electronic search. These articles were distributed among 20 reviewers for initial screening based on their relevance to the field of global EM. Another two reviewers searched the gray literature, yielding an additional 11 articles. All articles that were deemed appropriate by at least one reviewer and approved by their editor underwent formal scoring of overall quality and importance. Two independent reviewers scored all articles. Results: A total of 848 articles met our inclusion criteria and underwent full review. Sixty‐three percent were categorized as emergency care in resource‐limited settings, 23% as disaster and humanitarian response, and 14% as EM development. Twenty‐one articles received scores of 18.5 or higher out of a maximum score 20 and were selected for formal summary and critique. Inter‐rater reliability testing between reviewers revealed a Cohen's kappa of 0.344. Conclusions: In 2017, the total number of articles identified by our search continued to increase. Studies and reviews with a focus on infectious diseases, pediatrics, and trauma represented the majority of top‐scoring articles.